Social protection of fathers in multiple-child families - S. E. Titor (Вестник университета, 2022)
Statistics show that the number of large families in Russian Federation is not decreasing. The state takes sufficient measures to support such families. The status of a father with many children is also being transformed. Fathers with many children today have begun to assert their rights more, which inevitably leads to the need for their revision. This determines the relevance of this study. The article analyzes sociological studies of multiple-child families from the point of view of their property status, the ability to work, improve their qualifications and career opportunities. The opinion of large families themselves about the problems they have to face with is studied. The status of a father with many children is studied in the context of his labor rights. According to the results of the study, some measures are proposed to further protect of fathers’ with many children labor rights. The study is applicable to the demographic policy of Russia.